EFFECT OF DENSITY ON GROWTH AND SURVIVAL RATE OF BAUNG (Hemibagrus nemurus) IN AQUAPONIC SYSTEMS - Peli Swandi Tua Sinaga; Usman M.Tang; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT  Stocking density is an important thing to consider in fish culture.Increased density affects the physiological processes and behavior of fish in their space. One of the technological innovations applied is fish farming integrated with plants through the aquaponic system. This technology, in principle, aside from saving land and water use, also improves business efficiency through the use of nutrients from the leftovers and fish metabolism for aquatic plants and is one of the environmentally friendly fish culture systems.This research was conducted on November to December 2018 in the Hatchery of TIU (Technical Implementation Unit) of Aquaculture Department, Marine and Fishery Faculty, Riau University, Riau Province.The purpose of this study was to determine the best stocking density for growth and survival rate of baung fish (Hemibagrus nemurus) in the maintenance of aquaponic systems using water spinach vegetable species, with the treatment of fish stocking densities of 20 ind./m3, 25 ind./m3, 30 ind./m3and 35 ind./m3. The size of the fish used ± 4 cm, while water spinach plants used were 9 days old.The method used in this study is an experimental method using a completely randomized design (CRD) of a factor consisting of 4 levels of treatment with 5 replications so that 20 units of experiment are needed.The results of the study concluded that the baung fish with different stocking densities had a significant influence on growth, feed efficiency, feed conversion and survival rate of baung fish.The ideal stocking density for fish is 25 tails / cm3, with absolute weight growth of 2.94 g, absolute length growth of 3.80 cm, specific growth rate of 4.89% / day, feed efficiency of 73.90%, conversion feed of 1.35 and a survival rate of 94%.Aquaponic recirculation technology is able to maintain water quality and support the selection of baung fish.Keywords: Hemibagrus nemurus, Aquaponic, Stocking density